2013
DOI: 10.11622/smedj.2013022
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Prevalence of glucose intolerance, and associated antenatal and historical risk factors among Malaysian women with a history of gestational diabetes mellitus

Abstract: Singapore Med J 2013; 54(1) : 58 E r r atu m Prevalence of glucose intolerance, and associated antenatal and historical risk factors among Malaysian women with a history of gestational diabetes mellitus Chew W F, Rokiah P, Chan S P, Che e S S , Le e LF, Chan Y M Singapore Med J 2012; 53(12): 814-820 On page 815, Methods section, paragraph 2, lines 9-11, the correct sentence should be, "Therefore, the formula used for this study should be n = [1.96 2 × (0.126 × 0.874)]/ 0.05 2 , and the sample size needed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Some of these aforementioned factors have previously been found to be related to the onset of diabetes later in life in women with prior GDM, including an older age, a waist circumference ≥ 88 cm [28], and a higher BMI [30]. We did not, however, detect independent associations between insulin therapy during pregnancy and the later onset of AGR or dyslipidemia, as other studies have reported [28,29].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Some of these aforementioned factors have previously been found to be related to the onset of diabetes later in life in women with prior GDM, including an older age, a waist circumference ≥ 88 cm [28], and a higher BMI [30]. We did not, however, detect independent associations between insulin therapy during pregnancy and the later onset of AGR or dyslipidemia, as other studies have reported [28,29].…”
Section: Discussioncontrasting
confidence: 63%
“…Previous studies deal primarily with follow-up of patients with GDM. Furthermore, they focus on the risk of development of T2DM following delivery [27][28][29]. One study that assessed GDM women at both 3 and 12 months postpartum reported that 17.1% of those with NGT at 3 months progressed to AGR at 12 [30].…”
Section: Discussionmentioning
confidence: 99%